THE ANALYSIS OF OPTIMAL CRACK RATIO FOR PWR PRESSURE VESSEL CLADDING USING GENETIC ALGORITHM - Mike Susmikanti; Roziq Himawan; Jos Budi Sulistyo (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2018)
Several aspects of material failure have been investigated, especially for materials used in Reactor Pressure Vessel (RPV) cladding. One aspect that needs to be analyzed is the crack ratio. The crack ratio is a parameter that compares the depth of the gap to its width. The optimal value of the crack ratio reflects the material's resistance to the fracture. Fracture resistance of the material to fracture mechanics is indicated by the value of Stress Intensity Factor (SIF). This value can be obtained from a J-integral calculation that expresses the energy release rate. The detection of the crack ratio is conducted through the calculation of J-integral value. The Genetic Algorithm (GA) is one way to determine the optimal value for a problem. The purpose of this study is to analyze the possibility of fracture caused by crack. It was conducted by optimizing the crack ratio of AISI 308L and AISI 309L stainless steels using GA. Those materials are used for RPV cladding. The minimum crack ratio and J-Integral values were obtained for AISI 308L and AISI 309L. The SIF value was derived from the J-Integral calculation. The SIF value was then compared with the fracture toughness of those material. With the optimal crack ratio, it can be predicted that the material boundaries are protected from damaged events. It can be a reference material for the durability of a mechanical fracture event.Keywords: Fracture mechanics, RPV cladding, J-Integral, Stress Intensity Factor, Genetic Algorithm ANALISIS RASIO RETAK OPTIMAL UNTUK KELONGSONG BEJANA TEKAN PWR MENGGUNAKAN ALGORITMA GENETIKA. Banyak aspek kegagalan material telah diteliti, terutama untuk bahan yang digunakan pada kelongsong bejana tekan reaktor (RPV). Salah satu aspek yang perlu dianalisis adalah rasio retak. Rasio retak adalah parameter yang membandingkan kedalaman celah dengan lebarnya. Nilai optimal rasio retak mencerminkan ketahanan material terhadap patahan. Ketahanan material terhadap mekanika patahan ditunjukkan oleh nilai Stress Intensity Factor (SIF). Nilai ini dapat diperoleh dari perhitungan J-integral yang mengekspresikan tingkat pelepasan energi. Deteksi rasio retak dilakukan melalui perhitungan nilai J-integral. Algoritma Genetika (GA) adalah salah satu cara untuk menentukan nilai optimal suatu masalah. Tujuan dari penelitian ini adalah untuk menganalisis kemungkinan patah yang disebabkan oleh retak dengan menganalisis rasio retak baja tahan karat AISI 308L dan AISI 309L dengan GA. Bahan tersebut digunakan untuk kelongsong RPV. Rasio retak optimal dan nilai J-Integral diperoleh untuk AISI 308L dan AISI 309L. Nilai SIF berasal dari perhitungan J-Integral. Nilai SIF kemudian dibandingkan dengan ketangguhan retak material tersebut. Dengan rasio retak optimal, dapat diprediksi batas rasio retak sehingga terlindung dari kejadian patah. Hal ini dapat menjadi bahan referensi untuk ketahanan dari mekanika patahan.Kata kunci: Mekanika Patahan, Kelongsong Bejana Tekan Reaktor, J-Integral, Faktor Intensitas Tegangan, Algoritma Genetik